Prototype of Leak Detection using Blynk Application in IoT - Muhammad Afiq Zurkifli; SUBRAMANIAM, TAMIL SELVAN; Normah Zakaria; Azmanirah Ab Rahman (Research and Innovation in Technical and Vocational Education and Training, 2021)
Abstract: Leakage, Turbidity and Water Pressure Detectors Using IoT is a prototype developed to measure the level of water performance. The problem obtained is the problem of unconsciousness of water leakage in private home areas. In addition, the problem of quality caused by water pollution ensures that the water source obtained is safe to use. Furthermore, strong water pressure problems can also result in leaks in the water tank. Therefore, the purpose of this study is to develop a prototype of leak detection, turbidity and water pressure using IoT that will detect the problem as well as send water quality to users using the Blynk application. The three objectives of the study set are to design, develop products and test the prototype functionality of Leak Detector, Turbidity and Water Pressure Using IoT. The development of this prototype is based on the Design Thinking model which has five main phases namely empathy phase, defining phase, idea phase, prototype phase and testing phase. This model was chosen because it is an effective way of problem solving and very helpful in the development of prototype development. Based on the engineering analysis made, the water quality detector will detect whether the water is unconscious, and the problem of quality caused by the water source obtained is safe to use. In addition, raindrop detectors will detect water leaks in the event of a leak. While a water pressure detector will detect water for high and low water levels. Overall, the prototype produced has successfully met the objectives and the analysis made successfully demonstrates the functionality of this prototype. Keywords: Leak detection, IoT, Blynk, Design Thinking, Water Performance